Respostas

A melhor resposta!
2013-06-04T14:05:27-03:00

3 números consecutivos 

x, x + 1 e x + 2

sendo x + 2 o maior deles

3*(x + 2) = x + (x + 1)
3x + 6 = 2x + 1
3x - 2x = 1 - 6
x = - 5

Os números são:

x = - 5
x + 1 = - 5 + 1 = - 4
x + 2 = - 5 + 2 = - 3

(-5, -4 e -3

 

espero que ajude ^^

3 5 3
2013-06-04T14:08:30-03:00

3 números consecutivos 

x, x + 1 e x + 2

sendo x + 2 o maior deles

3*(x + 2) = x + (x + 1)
3x + 6 = 2x + 1
3x - 2x = 1 - 6
x = - 5

Os números são:

x = - 5
x + 1 = - 5 + 1 = - 4
x + 2 = - 5 + 2 = - 3

(-5, -4 e -3)

Valeu!!!

2 5 2